Manajemen Komunikasi Pemasaran antara Lembaga Zakat (Amil) kepada Penerima Zakat (Mustahik) - Habib Ismail; Farid Aji Prakosa; Khusnul Amalin (Universitas Nusantara PGRI Kediri, 2025)
Indonesia has great potential in collecting zakat as a country with the largest Muslim population. However, its distribution is still predominantly consumptive and has not been optimal in improving the welfare of mustahik. This study aims to determine the marketing communication management carried out by the Indonesian Zakat Initiative (IZI) Yogyakarta in the